Analysis of VEGFR-2 and PDGFR-β expression in canine splenic hemangiosarcoma to identify drug repositioning candidates - Vicente, Igor Simões Tiagua; de Moura, Fernanda Barthelson Carvalho [UNESP]; Rozolen, Juliana Moreira [UNESP]; dos Anjos, Denner Santos [UNESP]; Sobral, Renata Afonso; Alves, Carlos Eduardo Fonseca [UNESP] (Revista Brasileira de Medicina Veterinaria, 2024)
Splenic tumors are very common in dogs, and canine hemangiosarcoma (HSA) is one of the most important malignant splenic tumors. Surgery followed by chemotherapy (anthracycline-based protocols) is recommended for treating canine HSA; however, patients still do not achieve long-term survival. Therefore, this research aimed to assess vascular endothelial growth factor receptor-2 (VEGFR-2) and platelet-derived growth factor receptor-β (PDGFR-β) gene expression in formalin-fixed tissues, evaluate the quality of mRNA for quantitative polymerase chain reaction (qPCR) analysis and identify drug repositioning candidates based on VEGFR-2 and PDGFR-β. qPCR analysis identified the relative expression of heterogeneous VEGFR-2 and PDGFR-β, with samples showing no transcripts or very low expression and those with higher relative quantification for both genes. We then used immunohistochemistry to correlate the relative quantification of VEGFR-2 and PDGFR-β transcripts with respective higher protein expression to validate our results. In the next step, we evaluated drug repositioning candidates and identified small molecule inhibitors (i.e. sorafenib) and natural compounds (curcumin and resveratrol) with the ability to block VEGFR-2 and PDGFR-β genes. Overall, our results indicated that VEGFR-2 and PDGFR-β expression is highly variable among canine HSA samples and different drugs can block the expression of both genes. Therefore, a personalized approach could be useful for selecting anti-VEGFR-2 and PDGFR-β therapies and both genes are potential candidates for future oncological panels.
Keywords: dogs; drug repurposing; endothelial cells; spleen